Statistics for mining engineering - Czaplicki, Jacek M. (CRC Press/Balkema, 2014)
Many areas within mining engineering gather and use information that is statistical in nature. This information is provided by observing the realities of activities such as the operation of pieces of equipment and their systems, the processes of the development of mining works, the surface subsidence that accompanies underground mining, the displacement of rocks surrounding surface pits and underground drives and longwalls, etc.